It's Insulin - Wegmann, Dale R.; Eisenbarth, George S. (Journal of autoimmunity, 2000)
The realization that the majority of cases of insulin dependent diabetes mellitus (IDDM) are of an autoimmune etiology has led to an interest in the identification of antigens that are recognized in this proceess. Experimental evidence accumulated from human subject and the non-obese diabetic (NOD) mouse demonstrates that type 1A diabetes is associated with the presence of either antibody or T-cell responses to a number of defined antigens. These antigens include insulin, glutamic acid decarboxylase 65 (GAD65), ganglioside GM2-1, IA-2 (ICA512/IA-2), and others. The present discussion will focus on the relative roles of insulin vs. GAD65 as crucial autoantigens in the pathogenic immune response to beta cells in IDDM in mouse and man. These two antigens have been the most widely investigated in both the NOD mouse and in human subjects. Antibodies to these antigens have been identified as reliable serological markers for risk of Type 1 diabetes in humans. GAD65 and insulin have also been demonstrated to prevent or reduce the incidence of diabetes in NOD mice when administered by a variety of routes. A brief comparison of experimental results obtained with GAD65 and insulin is presented in Table 1. These results will be examined in more detail below.